Experience and Care Pathway of Patients with Lung Cancer: An Online International Survey - Pauline Frank; Julie Laurent; Lorraine Dallas; Pasquale Varriale; Andrew Ciupek (Oncology and Therapy, 2024)
Abstract Introduction This research sought to identify trends in the patient with lung cancer (LC) care pathway, experiences, and needs, across geographies and healthcare settings. Methods Patients living with LC for more than 18 years in nine countries completed an online survey covering these domains—demographic, disease, treatment, and patient preferences for information and support services. Recruitment was primarily from patient with LC communities on online platforms. Results A total of 1000 patients with LC completed the survey across Europe (49%), North America (29%), and Asia (22%). Demographics of participants were different to what has been reported in literature—there were a lower proportion of type non-small cell lung cancer (NSCLC), a higher proportion of type small cell lung cancer (SCLC), a higher rate of early-stage diagnosis, and a younger population. There were 56% male participants. Although physicians were the main stakeholders influencing treatment choice and quality of life (QoL) discussions, the patient’s family/relatives ranked highly as important stakeholders. The top reasons patients reported choosing a treatment were related to efficacy, and hesitation to start a treatment was related to concerns about side effects. QoL was an important factor in both cases. Patients are impacted physically, socially, and mentally—50% report an impact on employment status, 48% report daily difficulties in mental well-being, and 64% have received psychological support or would like to. Disparities were observed across countries in genetic/biomarker testing completed or planned (30–88%) and being asked to participate in clinical trials (15–49%), which reflects the status of how different patient with LC care pathways have adopted innovation in LC care. Conclusion Both medical and external factors impact experiences and outcomes of patients living with LC, including the role of family in treatment and QoL discussions. There are intercountry differences in knowledge and disease management.